RECONSTRUCTION OF THE PENAL SYSTEM POLICY AGAINST CHILDREN OF CYBER CRIME PERPETRATORS BASED ON RESTORATIVE JUSTICE IN THE REFORM OF NATIONAL CRIMINAL LAW - Dinata, Umar; Aksar, Aksar; Hendrawan, Heru (LPPM, Universitas Muhammadiyah Riau, 2026)
The development of information technology has given rise to various forms of cyber crime involving children as perpetrators. This condition is a new challenge in the juvenile criminal justice system in Indonesia. The penal system that is still oriented towards punishment is considered not to fully reflect the principles of child protection and the best interests of the child. This study aims to analyze the penal policy for children of cyber crime offenders and reconstruct the restorative justice-based criminal model in the reform of national criminal law. The research method used is normative legal research with legislative, conceptual, and case approaches. The results of the study show that the application of restorative justice to children of cyber crime perpetrators still faces various obstacles, both in terms of regulations, law enforcement officials, and the rapid development of digital technology. Therefore, it is necessary to reconstruct a criminal policy that emphasizes rehabilitation, diversion, digital education, and victim recovery in order to realize a humane and fair national criminal law system.